Counsellors, Counselling, and Social Justice: The Professional is Political - Arthur, Nancy; Collins, Sandra (Canadian Journal of Counselling and Psychotherapy, 2014)
This introduction to the Counselling and Social Justice special issue highlights the centrality of social justice in counselling, the negative impact of social injustices and cultural oppression on client well-being, and the importance of expanding professional focus and counsellor roles to engage in system-level change, with and on behalf of our clients. The Culture-Infused Counselling model provides a conceptual framework for integrating culture and social justice into all aspects of counselling practice. The contributions to the special issue bring to life ways to apply social justice principles with diverse client populations, in different contexts, nationally and internationally.